Construction of iron-mineralized black phosphorene nanosheet to combinate chemodynamic therapy and photothermal therapy - Zhaoqing Shi; Jing Tang; Chuchu Lin; Ting Chen; Fan Zhang; Yuxing Huang; Ping Luan; Zhuo Xin; Qianqian Li; Lin Mei (Taylor & Francis Group, 2022)
Chemodynamic therapy (CDT) by triggering Fenton reaction or Fenton-like reaction to generate hazardous hydroxyl radical (•OH), is a promising strategy to selectively inhibit tumors with higher H2O2 levels and relatively acidic microenvironment. Current Fe-based Fenton nanocatalysts mostly depend on slowly releasing iron ions from Fe or Fe oxide-based nanoparticles, which leads to a limited rate of Fenton reaction. Herein, we employed black phosphorene nanosheets (BPNS), a biocompatible and biodegradable photothermal material, to develop iron-mineralized black phosphorene nanosheet (BPFe) by in situ deposition method for chemodynamic and photothermal combination cancer therapy. This study demonstrated that the BPFe could selectively increase cytotoxic ·OH in tumor cells whereas having no influence on normal cells. The IC50 of BPFe for tested tumor cells was about 3-6 μg/mL, which was at least one order of magnitude lower than previous Fe-based Fenton nanocatalysts. The low H2O2 level in normal mammalian cells guaranteed the rare cytotoxicity of BPFe. Moreover, the combination of photothermal therapy (PTT) with CDT based on BPFe was proved to kill tumors more potently with spatiotemporal accuracy, which exhibited excellent anti-tumor effects in xenografted MCF-7 tumor mice models.